IL-4: PREDIKTOR ANTI INFLAMASI PADA STROKE ISKEMIK ? - Lucia Herminawati; Julius July (Medicinus, 2018)
The brain ischemia due to vascular occlusion, especially in the main cerebral artery, could trigger the microglia as a natural immune cell in the brain. These activated microglia will turn up the inflammation cascade in the ischemic area. Interleukin-4 (IL-4) has a vital role in the microglial alteration to become an anti-inflammatory phenotype, which wind up the expression of MHC II and CD11c. Moreover, previous studies has supported that the stimulation of IL-4 in the culture of microglia/macrophage will produce this kind of “alternative” phenotype or neuroprotective phenotype, through the fall of TNF and rise of IGF-1. However, only a few have discussed the role and profile of IL-4 in ischemic stroke. This review article will cover the possibility of IL-4 role as an anti-inflammatory predictor in ischemic stroke.Keywords: Interleukin-4, microglia, ischemic stroke, inflammation